Analysis of Participation in Traditional Egrang Games on Balance in Elementary School Students - Nadhea Ayu Rahmawati; Dhias Fajar Widya Permana (Universitas Negeri Semarang, 2025)
There are various kinds of traditional game toys, such as bamboo stilts, which have strong educational and motor skills value, particularly for static and dynamic balance training, coordination, and core muscles. Early engagement with digital objects will attenuate participation in traditional forms of gaming. This study aims to examine the relationship between traditional stilts games and balance ability for elementary school children. The research used a quantitative, cross-sectional design and purposively selected 49 grade V students from Musuk Public Elementary School , Musuk District, Boyolali Regency as the study’s sample. Participation in the egrang games was categorized as low, medium, or high. Balance of the body was, however, measured by the Static Stork and Dynamic Beam Scale. The data were compared using descriptive statistics, normality and homogeneity tests, and Pearson’s correlation at the p < 0.05 significance level. Results The frequency of playing e-grang games was significantly associated with static balance (r = 0.605; p = 0.000), but not with dynamic balance (r = − 0.276; p = 0.055). It can be said that the traditional game (egrang) is more effective at improving body steadiness when the body is static than when it is dynamic. The development of the egrang game can be used as one form of active learning on static balance among elementary school students.